1997
DOI: 10.1177/108835769701200301
|View full text |Cite
|
Sign up to set email alerts
|

Communications Directed to Students with Severe and Profound Disabilities

Abstract: Two studies were conducted to examine characteristics of teacher communications to students who have severe and profound disabilities. Of particular interest was the influence of various factors on the methods of communication teachers used when they were conveying information to students who lacked language abilities. It appeared that the forms of communication teachers selected were less related to the student's communicative ability or responsiveness to particular forms than they were to the teacher's inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The present paper explores the importance of validating communication, and in particular, of working together with family members and significant others to share information in order to build up an accurate profile of how and what an individual communicates. This need has been further highlighted by studies which have suggested that staff may be overestimating learners' understanding of verbal cues and have difficulty adjusting their communication to the person's level (Stillman et al. 1997; McConkey et al.…”
Section: Introductionmentioning
confidence: 99%
“…The present paper explores the importance of validating communication, and in particular, of working together with family members and significant others to share information in order to build up an accurate profile of how and what an individual communicates. This need has been further highlighted by studies which have suggested that staff may be overestimating learners' understanding of verbal cues and have difficulty adjusting their communication to the person's level (Stillman et al. 1997; McConkey et al.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the person may acquiesce rather than disagree with the interpretation by another, or may show a response bias, especially when the question is not understood or the answer is not known. Other studies showed that it can be hard for staff members to adjust their level of communication to the correct level, and that staff members may overestimate the ability of the person with learning disabilities to understand verbal cues (Stillman et al . 1997; McConkey et al .…”
Section: Introductionmentioning
confidence: 99%